Circulating extracellular vesicle‐encapsulated HULC is a potential biomarker for human pancreatic cancer. Issue 1 (5th December 2019) - Takahashi, Kenji; Ota, Yu; Kogure, Takayuki; Suzuki, Yuko; Iwamoto, Hidetaka; Yamakita, Keisuke; Kitano, Yohei; Fujii, Satoshi; Haneda, Masakazu; Patel, Tushar; Ota, Tsuguhito
Abstract: The role of long noncoding RNAs (lncRNAs) in the epithelial‐mesenchymal transition (EMT) in pancreatic ductal adenocarcinoma (PDAC) is unclear. Some lncRNAs can be transferred by extracellular vesicles (EVs) and have potential as biomarkers. Here, we identify an lncRNA that could serve as a biomarker for PDAC and show the functional roles of the lncRNA. Expression profiling of lncRNAs revealed that highly upregulated in liver cancer (HULC) was highly expressed, and induced, by transforming growth factor‐β in PDAC cells and their EVs. Knockdown of HULC decreased PDAC cell invasion and migration by inhibiting the EMT. Thus, HULC could be transferred by EVs, and promote EMT, invasion, and migration in recipient PDAC cells. To assess the roles of HULC, PDAC cell xenografts in nude mice were established. Knockdown of HULC in PDAC cells implanted in mice inhibited tumor growth. Moreover, microRNA‐133b suppressed PDAC cell invasion and migration by inhibiting the EMT through targeting HULC. Furthermore, serum samples were obtained from 20 PDAC and 22 intraductal papillary mucinous neoplasm (IPMN) patients, as well as 21 healthy individuals. Analysis of serum EV HULC expression by digital PCR showed that HULC expression was significantly increased in PDAC patients compared to healthy individuals or IPMN patients. Additionally, HULC showed good predictive performance for discriminating PDAC, suggesting that the analysis of EV‐encapsulated HULC would contribute to the diagnosis for human PDAC. Extracellular vesicle‐transported HULC promotes cell invasion and migration by inducing the EMT, and microRNA‐133b suppresses the EMT by targeting HULC. Extracellular vesicle‐encapsulated HULC could be a potential circulating biomarker for human PDAC. Abstract : Extracellular vesicle HULC can regulate cell invasion and migration through induction of epithelial‐mesenchymal transition. Extracellular vesicle HULC could compare favorably with CA19‐9 as a novel biomarker in liquid biopsy for human pancreatic ductal adenocarcinoma.